Exploratory biomarker analysis for treatment response in KRAS wild type metastatic colorectal cancer patients who received cetuximab plus irinotecan. Issue 1 (December 2015) - Kim, Seung; Ahn, Tae; Lee, Eunjin; Do, In-Gu; Lee, Su; Park, Se; Park, Joon; Park, Young; Lim, Ho; Kang, Won; Kim, Suk; Lee, Jeeyun; et al.
Abstract Background More than half of the patients selected based onKRAS mutation status fail to respond to the treatment with cetuximab in metastatic colorectal cancer (mCRC). We designed a study to identify additional biomarkers that could act as indicators for cetuximab treatment in mCRC. Methods We investigated 58 tumor samples from wild typeKRAS CRC patients treated with cetuximab plus irinotecan (CI). We conducted the genotyping for mutations in eitherBRAF orPIK3CA and profiled comprehensively the expression of 522 kinase genes. Results BRAF mutation was detected in 5.1 % (3/58) of patients. All 50 patients showed wild type PIK3CA. Gene expression patterns that categorized patients with or without the disease control to CI were compared by supervised classification analysis.PSKH1, TLK2 andPHKG2 were overexpressed significantly in patients with the disease control to IC. The higher expression value ofPSKH1 (r = 0.462, p < 0.001) andTLK2 (r = 0.361, p = 0.005) had the significant correlation to prolonged PFS. Conclusion The result of this work demonstrated that expression nature of kinase genes such as PSKH1, TLK2 and PHKG2 may be informative to predict the efficacy of CI in wild type KRAS CRC. Mutations in either BRAF or PIK3CA were rare subsets in wild type KRAS CRC.